Impact of deprivation in the family on the manifestation of aggressiveness and hostility of adolescents (Actual Problems of Psychology in Educational Institutions, 2022)
In this article various approaches for understanding such terms as aggression, aggressiveness and hostility in the view of modern psychology are analysed. The research results on the acts of aggression and hostility of the teenagers being raised in children’s homes are examined here. The article places a special focus on the forms of their aggressive behaviour and establishes the linkage between hostility and the aggressive behaviour of the inmates of children’s homes. Alongside this article covers the reasons of an aggressive model of teenagers’ behavior and involves some areas of corrective work to decrease their hostility and auto-aggressive behaviour.